A vocational education and livelihood start-up facility for communities by the Manila Port - Pastor, Maria Montserrat M.; Gines, Leonido, Jr. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Manila's history and geography have paved the way for its growth into one of the most highly globalized cities in the country. As a home to the Manila Harbor, the City of Manila has transitioned into a trading capital an economic hub with direct access to the global capital market. At the same time, however, it is home to communities that suffer from an extremely high incidence of poverty and unemployment. On the basis of this blend of industry and community within common ground, this proposed multi-functional livelihood facility within the Port of Manila offers a solution to the lack of livelihood opportunities for the marginalized while capitalizing on the global nature of the area. It seeks to bridge the gap between local and global, and to use architecture to benefit both the community and the industry through vocational education and sectoral workforce development grounded on the functions of the global industry, as it integrated the local settlements into the labor market while serving as a threshold between formal and informal within the port area.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Architecture and globalization; Livelihood facilities -- Manila; Vocational education -- Manila